Respuesta :

Space

Answer:

n = -3

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Step-by-step explanation:

Step 1: Define equation

3(-2 - n) = -9 - 4n

Step 2: Solve for n

  1. Distribute 3:                    -6 - 3n = -9 - 4n
  2. Add 4n to both sides:     -6 + n = -9
  3. Add 6 to both sides:       n = -3

Step 3: Check

Plug in n to verify it's a solution.

  1. Substitute:                    3(-2 - -3) = -9 - 4(-3)
  2. Simplify:                        3(-2 + 3) = -9 - 4(-3)
  3. Add:                              3(1) = -9 - 4(-3)
  4. Multiply:                        3 = -9 + 12
  5. Add:                              3 = 3